2023
DOI: 10.1093/ecco-jcc/jjac190.0935
|View full text |Cite
|
Sign up to set email alerts
|

P805 Selnoflast, a potent NLRP3 inhibitor - results from a phase 1b experimental medicine study in patients with Ulcerative Colitis

Abstract: Background The Nucleotide-binding oligomerization domain, leucine rich repeat and pyrin domain containing 3 (NLRP3) inflammasome is a driver of caspase 1-dependent release of IL-1β and IL-18 and has been identified as a potential drug target for ulcerative colitis (UC) (Tourkochristou et al. 2019). Selnoflast (RO7486967) is an orally active, potent, selective, and reversible small molecule NLRP3 inhibitor. To assess whether NLRP3 is a driver of inflammation and more specifically of IL-1β prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the Phase Ib clinical trial for UC, the examination of sigmoidal tissue biopsies, single-cell RNA sequencing, and additional biomarker analyses revealed no notable discrepancies in the expression of the IL-1β gene signature between the treatment and control groups. 32 This implied that the use of selnoflast to target NLRP3 inflammasome may offer limited therapeutic advantages in mitigating inflammation in UC, which could be a potential explanation for Roche's delay in commencing Phase II clinical trials. Emlenoflast, a brain-penetrant NLRP3 inflammasome inhibitor developed at Roche, completed its Phase I clinical trial for CAPS in 2020 (NCT04015076).…”
Section: Nlrp3 Inflammasome Drug Candidates Under Clinical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Phase Ib clinical trial for UC, the examination of sigmoidal tissue biopsies, single-cell RNA sequencing, and additional biomarker analyses revealed no notable discrepancies in the expression of the IL-1β gene signature between the treatment and control groups. 32 This implied that the use of selnoflast to target NLRP3 inflammasome may offer limited therapeutic advantages in mitigating inflammation in UC, which could be a potential explanation for Roche's delay in commencing Phase II clinical trials. Emlenoflast, a brain-penetrant NLRP3 inflammasome inhibitor developed at Roche, completed its Phase I clinical trial for CAPS in 2020 (NCT04015076).…”
Section: Nlrp3 Inflammasome Drug Candidates Under Clinical Evaluationmentioning
confidence: 99%
“…ZYIL1, an oral NLRP3 inhibitor developed by Zydus for CAPS treatment, showed good tolerability and safety in the Phase IIa proof-of-concept (POC) study, while no anomalies were observed in renal and liver function tests (NCT05186051). , Selnoflast, another orally available NLRP3 inhibitor, has completed a Phase I clinical trial for the treatment of CAPS (NCT04086602) and is being explored by Roche for other inflammatory conditions, including ulcerative colitis (UC), chronic obstructive pulmonary disease, and idiopathic PD (NCT05924243). In the Phase Ib clinical trial for UC, the examination of sigmoidal tissue biopsies, single-cell RNA sequencing, and additional biomarker analyses revealed no notable discrepancies in the expression of the IL-1β gene signature between the treatment and control groups . This implied that the use of selnoflast to target NLRP3 inflammasome may offer limited therapeutic advantages in mitigating inflammation in UC, which could be a potential explanation for Roche’s delay in commencing Phase II clinical trials.…”
Section: Nlrp3 Inflammasome Drug Candidates Under Clinical Evaluationmentioning
confidence: 99%
“…Figure shows the structures of glyburide, CP-456,773, and various other selective NLRP3 inflammasome inhibitors, all of which share some structural features with CP-456,773. ZYIL-1, selnoflast, , emlenoflast, DFV890 , and GDC-2394 have all progressed to testing in human clinical trials. Although there are multiple molecules undergoing clinical evaluation, no selective NLRP3 inhibitor has been approved for the market.…”
Section: Introductionmentioning
confidence: 99%